Behavioral and biochemical effects of a formulation of the traditional Chinese medicine, Kai-Xin-San, in fatigued rats - HU, YUAN (D.A. Spandidos, 2013)
The present study was designed to evaluate the anti-fatigue activity and the behavioral and biochemical effects of Kai-Xin-San (KXS) extracts on fatigued rats. The rats were randomly divided into six groups: untreated control (UC), running control (RC), RC treated with 13 mg/kg/day modafinil and RC treated with KXS at dosages of 125, 250 and 500 mg/kg/day, respectively. The treatments were administered orally. Anti-fatigue activity was assessed using the treadmill running test and serum biochemical parameters were determined using an autoanalyzer and commercially available kits. Furthermore, the standardization of the KXS extracts was ensured using a high-performance liquid chromatography (HPLC)-fingerprint. The extracts were shown to increase exhaustive running time in the treadmill running test and reverse the fatigue-induced reduction in hepatic/muscle glycogen and testosterone, in addition to reducing the lactate dehydrogenase (LDH), serum urea nitrogen (SUN), blood lactic acid (BLA) and β-endorphin levels in the serum of the fatigued rats. Moreover, the extracts enhanced superoxide dismutase (SOD) activity and decreased the malondialdehyde (MDA) levels in the serum of the fatigued rats. The results of this preliminary study indicated that KXS exhibits anti-fatigue activity. This was reflected in the effects on the biochemical markers for fatigue.